Optimizing placement of field experience program: An integration of MOORA and rule-based decision making - Okfalisa, Okfalisa; Hafsari, Rizka; Nawanir, Gusman; Toto, Saktioto; Yanti, Novi (Universiti Putra Malaysia, 2021)
The lack of optimality in the Field Experience Program (FEP) placement has affected universities’ educational services to the stakeholders. Bringing together the stakeholders’ needs, university capacities, and participants’ willingness to quality and quantity is not easy. This study tries to optimize the placement of FEP by considering the interests of multiple perspectives through the application of Multi-Objective Optimization on the Basic of Ratio Analysis (MOORA) and Rule-Based methods in the form of a decision-making model. MOORA ranked the students based on the FEP committee’s perspective and other criteria, such as micro-teaching grades, final GPAs, study programs, number of credits, and student addresses. Meanwhile, the school perspective was ordered based on its accreditations, levels, types, facilities, and performances. To achieve the optimal recommendation of FEP placement, the integration of MOORA and Rule-based intertwined the requirement of such perspectives. A prototype of the system recommendation is then acquired to simplify the decision-making model. As adjudications, a survey from twenty stakeholders evidenced around 86.92% of system user acceptances. The confusion matrix testing defines the accuracy of this method reaches 78.33%. This paper reveals that the recommendation model has been successfully increasing the effectiveness of decision making in FEP placement under the needs and expectations of the entire stakeholders.